Conflict of Regulations in the Offering of Special Mining Business License Areas (WIUPK) Against Legal Certainty for Religious Organization-Owned Enterprises - Safriansyah Yanwar Rosyadi; Azis Budianto (Syntax Idea)
This study discusses policy reform in mining management in Indonesia, particularly regarding the offering of Special Mining Business License Areas (WIUPK) to Religious Organization-Owned Enterprises. Although existing regulations aim to improve governance in the mining sector, the enforcement of Article 83A in Government Regulation No. 25 of 2024 has instead resulted in ambiguity and legal uncertainty, as it is inconsistent with higher laws. This research recommends the need for regulatory revisions to create legal certainty, enhance the capacity of resource management by Religious Organizations, and adopt an inclusive approach in decision-making to ensure that mining management can be conducted responsibly and sustainably, providing optimal benefits for society and the environment